The Righteous paying for the Sinners? Analyzing the Amendments to the Arbitration Rules Against the Peruvian State - Rabines Matta, Rodrigo (2020)
In recent years, there have been many cases of corruption in arbitrations with the Peruvian state. As a result of them, the country has been forced to pay millionaire sums. In order to solve these problems, the Peruvian government issued Emergency Decree 020-2020, which modified the Legislative Decree 1071, Legislative Decree that regulates arbitration, in relation to arbitrations with the State.In this article, the author explains the reasons why these modifications have not been effective to solve the real problem for which Decree was published: avoid corruption in arbitration with the Peruvian State.